Geologic mapping and structural evolution of the Deadman Creek thrust in the Sangre de Cristo Range, southern Colorado - Primus, Miriam, author; Singleton, John, advisor; Harrison, Lauren, committee member; Ridley, John, committee member; Szymanski, Erika, committee member (Colorado State University. Libraries, 2026)
The western flank of the Sangre de Cristo Range in southern Colorado contains exposures of Proterozoic gneisses and granitoids that are locally thrust over slivers of Mississippian, Devonian, and Ordovician sedimentary rocks (MDO) and intruded by Oligocene granodiorite to diorite stocks and aplite dikes. These rocks record a complex geologic history that includes folding and faulting related to Laramide contraction and normal faulting and magmatism associated with Rio Grande rift extension. We investigated this multistage deformation with detailed geologic mapping and kinematic analysis of sheared rocks related to the Deadman Creek thrust – a top-NE directed thrust fault that juxtaposes Proterozoic crystalline rocks in the hanging wall over MDO in the footwall. Where the Deadman Creek thrust is best exposed away from the range front, it records top-NE contractional shear primarily localized in mylonitic MDO. This structure has been deformed by subsequent NE-vergent fault-propagation folds, locally reactivated as an extensional shear zone, and later dissected by brittle-plastic normal faults. One of these normal faults, designated as the Short Creek fault, is localized on the steep to moderately NE-dipping folded limb of the Deadman Creek thrust. Along the western flank of the range subhorizontal to gently-SW dipping mylonite zones (herein named the Duncan shear zone) in the footwall and hanging wall of the Deadman Creek thrust consistently record top-SW sense shear, opposite of the Laramide contractional regime. These zones are locally 10s of meters thick and are characterized by plastic deformation of quartz, brittle deformation of feldspar, and extensive chloritization, indicating greenschist facies deformation conditions. Quartz crystallographic preferred orientation data from mylonites in these zones are consistent with top-SW shear as well as local coaxial strain, and c-axis opening angles indicate deformation temperatures ranging from ~300–500° C. The thickest mylonite zones are found proximal to locally strained range-front Oligocene diorite and granodiorite intrusions, rather than along the contact of the Deadman Creek thrust, suggesting these mylonites are associated with magma emplacement. Zircon U-Pb data from one of these mylonitic intrusions yielded a date of 27.9 ± 0.3 Ma. Additionally, one of the NE-dipping brittle-plastic normal faults that cuts the Deadman Creek thrust involves an aplite intrusion with a 26.2 ± 0.3 Ma zircon U-Pb date. We interpret the top-SW shear zones and the brittle-plastic normal faults to record the earliest stages of Rio Grande rift extension that was coeval with magmatism and preceded development of the range-bounding Sangre de Cristo normal fault system in the Miocene.
Zip file contains 7 dataset spreadsheets, 1 MATLAB code file, 1 R script file, and Plate 1 PDF.